Primary Uterine Hemangiosarcoma in a Thoroughbred: A Case Report - Segabinazzi, Lorenzo G.T.M. [UNESP]; Apolonio, Emanuel V.P. [UNESP]; Tongu, Eriky A. [UNESP]; Paccola, Walnei; Vianna, Denise; Fonseca-Alves, Carlos E. [UNESP]; Alvarenga, Marco A. [UNESP] (Elsevier, 2021)
A 1.8-year-old maiden Thoroughbred filly, without previous history of mating or reproductive management, was referred for clinical inspection due to the presence of sanguineous vaginal discharge and severe abdominal pain. Transrectal palpation indicated uterine asymmetry, and transrectal ultrasonography revealed a mass near the cervix measuring 8.3 cm in diameter, with heterogeneous echogenicity, a trabeculated center, and a well-defined hyperechoic border. Smaller masses surrounded the larger uterine mass. During the examination, the mare expelled a uterine mass through the vulva. Histological and immunohistochemical (CD31 and Factor VIII) examinations of the expelled mass suggested a diagnosis of hemangiosarcoma. Therefore, a therapeutic hysterectomy was performed, and examinations of the uterine tissue confirmed the diagnosis. However, the mare was euthanized 2 weeks later due to postoperative complications. The animal was subjected to necropsy, and intestinal adhesions in the surgical incision were diagnosed as postoperative complications. No other neoplasms were found during necropsy, establishing the primary origin of the tumor. This case study presents the first known report of uterine hemangiosarcoma in an equine species.
Keywords: Angiosarcoma; Equine; Reproduction; Tumor